The Art of Leading Change : Ten Perspectives on the Messiness of Ministry - Bonem, Mike (Book collections on Project MUSE., 2022)
The Art of Leading Change is all about people. We can't do the work God has called us to do without people, but it's those very people that make change difficult and messy. The book offers ten vital perspectives for leading change in churches and ministries. The path to change is never easy, but learning the art of change can improve the journey.